Putusan Mahkamah Konstitusi yang Bersifat Mengatur (Positive Legislature) dalam Upaya Menghadirkan Keadilan Substantif - Indra Fatwa (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2020)
Abstract This research is a normative study, taking into account and referring to the laws and regulations and decisions of the related Constitutional Court. The problems examined are: First, does the Constitutional Court have the authority to make decisions that are positive legislature? Second, whether the reasons and considerations of the Constitutional Court judges made a positive legislature decision in decision No. 14 / PUU-XI / 2013? The results showed that: a. The Constitutional Court is normatively not authorized to issue positive legislature decisions. However, on the basis of efforts to bring substantive justice to the community, in several decisions the Constitutional Court Judges felt the need to make legal breakthroughs. b. The reasons and considerations of the Constitutional Court Justices in the decision No. 14 / PUU-XI / 2013 to make a regulatory decision is a consideration of insufficient time for legislators to make new rules if the decision is carried out at that time. Given that the General Election stage was already underway.